2006
DOI: 10.1002/cncr.21929
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interferon γ1b immune enhancement in 20 patients with hematologic malignancies and systemic opportunistic infections treated with donor granulocyte transfusions

Abstract: BACKGROUNDThe response to antifungal therapy alone often is suboptimal in patients with cancer who have therapy‐refractory neutropenia, and even donor‐derived granulocyte transfusions (GTX) are not always successful. The authors evaluated the safety and efficacy of immune enhancement using recombinant interferon γ1b (rIFN‐γ1b) in patients with cancer who received GTX for refractory, systemic, opportunistic infections.METHODSTwenty recipients of high‐dose donor GTX (≈5.5 × 1010 neutrophils per transfusion) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…Granulocyte transfusions have been more widely used in recent years as adjuvant therapy. 5 We found that more than one third of the patients with HHV-6 DNAemia had received such transfusions.…”
Section: 4mentioning
confidence: 76%
“…Granulocyte transfusions have been more widely used in recent years as adjuvant therapy. 5 We found that more than one third of the patients with HHV-6 DNAemia had received such transfusions.…”
Section: 4mentioning
confidence: 76%
“…In a similar animal model, it was shown that NK cell-derived IFN-g was the protective factor against IA (8,9). Clinical data confirmed an antifungal and, more specifically, the anti-Aspergillus activity of IFN-g (7,(10)(11)(12)(13)(14). These studies attributed the beneficial effect of IFN-g to its immunoregulatory role with phagocytes of the innate immune system, which are conventionally involved in the host defense against A. fumigatus (11,15).…”
Section: N Atural Killer Cells Are Cd56mentioning
confidence: 79%
“…Additionally, there was no difference in the neutrophil response to the first or subsequent GT in any single recipient, suggesting that antineutrophil immunization of the recipient did not occur or was not clinically relevant. Concomitant cytokine therapy in addition to G-CSF to enhance the function of transfused neutrophils, such as recombinant IFN-g1b, has shown promising results, [20][21][22] but detection or pharmacological stimulation of neutrophil function were not part of this study, which relied on neutrophil counts and clinical performance parameters. Peripheral blood counts might be an inadequate surrogate marker to assess the efficacy of GT because neutrophil tissue infiltration at the site of infection precedes the peripheral blood ANC increment.…”
Section: Nsmentioning
confidence: 99%